Fabrication of room temperature continuous-wave operation GaN-based ultraviolet laser diodes *Projects the supported by the National Key R&D Program of China (Nos. 2016YFB0401801, 2016YFB0400803), the National Natural Science Foundation of China (Nos. 61674138, 61674139, 61604145, 61574135, 61574134, 61474142, 61474110, 61377020, 61376089), the Science Challenge Project (No. JCKY2016212A503), and the One Hundred Person Project of the Chinese Academy of Sciences. (June 2017) - Zhao, Degang; Yang, Jing; Liu, Zongshun; Chen, Ping; Zhu, Jianjun; Jiang, Desheng; Shi, Yongsheng; Wang, Hai; Duan, Lihong; Zhang, Liqun; Yang, Hui
Abstract: Two kinds of continuous-wave GaN-based ultraviolet laser diodes (LDs) operated at room temperature and with different emission wavelengths are demonstrated. The LDs epitaxial layers are grown on GaN substrate by metalorganic chemical vapor deposition, with a 10 × 600 μ m 2 ridge waveguide structure. The electrical and optical characteristics of the ultraviolet LDs are investigated under direct-current injection at room temperature. The stimulated emission peak wavelength of first LD is 392.9 nm, the threshold current density and voltage is 1.5 kA/cm 2 and 5.0 V, respectively. The output light power is 80 mW under the 4.0 kA/cm 2 injection current density. The stimulated emission peak wavelength of second LD is 381.9 nm, the threshold current density the voltage is 2.8 kA/cm 2 and 5.5 V, respectively. The output light power is 14 mW under a 4.0 kA/cm 2 injection current density.